Paper cut : an exploration into the contemporary world of papercraft art and illustration - Gildersleeve, Owen (Beverly, MA : Rockport Publishers, 2014)
Paper Cut is a unique perspective into one of the most exciting fields of contemporary illustration. With contributions from 30 of the top papercraft illustrators, showcasing their amazing works and delving into their craft, this book will awe and inspire you. Author Owen Gildersleeve explores why these artists love papercraft, how they use it and what makes their work unique. See their ideas, inspirations and process in 250 full color photos that includes a range of interesting textured colored paper stocks dotted throughout. See exclusive works from designers like Chrissie MacDonald, Hattie Newman, Peter Callesen, Kyle Bean Helen Friel, Rob Ryan, Jeff Nishinakaand more!
-- Cover -- Title Page -- Contents -- Preface -- Introduction -- Featured Artists -- Andersen M Studio -- Kyle Bean -- Yulia Brodskaya -- Bianca Chang -- Le Creative Sweatshop -- Elise -- Alexis Facca -- Helen Friel -- Mayuko Fujino -- Marc Hagan-Guirey -- Lobulo -- Chrissie Macdonald -- The Makerie -- Stuart McLachlan -- Motherbird -- Helen Musselwhite -- Hattie Newman -- Jeff Nishinaka -- Eiko Ojala -- Ciara Phelan -- Rob Ryan -- Shotopop -- Mandy Smith -- Fideli Sundqvist -- Zim and Zou -- About the Author -- Contributors.
Keywords: Paper art -- 21st century